Iowa RBA, September 20-24, 1999 - Fuller, James Let al; Iowa Ornithologists' Unionet al (1999)
Six emails of Iowa RBA updates for September 20-24, 1999. Highlights of the updates include sightings of a Sharp-tailed Sandpiper, Brown Pelican, a Yellow-crowned Night Heron, a Black-crowned night Heron, and a Marbled Godwit. Epson - sheet feed/flatbed